Simone Weil: The Notion of Vocation - Jakimčikaitė, Inga (Religija ir kultūra, 2014)
This article deals with the notion of vocation of the 20th century French philosopher and mystic Simone Weil. It is shown how Weil’s choices of life had reflected in her philosophy and led her to intelectual vocation, which is revealed through a relation with the other. Weil’s amiability to all religions, especially Christianity, and her intelectual vocation made her not only question everything, but to feel outer and inner pressure as well. However, she found liberation in philosophical reflections and mystical experiences, where she perceived her vocation as not chosen, but fated by God. By keeping pure and focused attention Weil escapes from psychological and physical pain and affords to love her neighbor here and now. This love costs self-neglection and decreation. Weil’s notion of vocation reveals itself in the relation with the self and the other.